2010
DOI: 10.3109/09553000903564034
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput antibody-based assays to identify and quantify radiation-responsive protein biomarkers

Abstract: Purpose After a radiological ‘dirty bomb’ incident in a major metropolitan center, substantial numbers of people may be exposed to radiation. However, only a fraction of those individuals will need urgent medical attention. Consequently, a rapid screening test is needed to identify those people who require immediate treatment. Material and methods Ten normal human cell lines were screened by enzyme-linked immunosorbent assay (ELISA) for the expression of a dozen secreted cytokines that have been reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In this study, we expand upon earlier published observations of that have reported on the urinary and serum response of the mouse (Amendola et al 2006; Lee et al 2007; Tyburski et al 2008; 2009; Ossetrova et al 2010; Partridge et al 2010; Chen et al 2011) and rat(Randic & Supek 1961; Porciani et al 2001; Lanz et al 2009; Johnson et al 2011; Tang et al 2013; Zhang et al 2014) to γ radiation exposures. Using Ultra-Performance ® liquid chromatography (UPLC) in conjunction with time-of-flight mass spectrometry (TOFMS), we analyzed urine collected from rats prior to and at four time points after exposure to six different doses of gamma radiation ranging from 0.5 to 10 Gy at high dose rate.…”
Section: Introductionmentioning
confidence: 58%
“…In this study, we expand upon earlier published observations of that have reported on the urinary and serum response of the mouse (Amendola et al 2006; Lee et al 2007; Tyburski et al 2008; 2009; Ossetrova et al 2010; Partridge et al 2010; Chen et al 2011) and rat(Randic & Supek 1961; Porciani et al 2001; Lanz et al 2009; Johnson et al 2011; Tang et al 2013; Zhang et al 2014) to γ radiation exposures. Using Ultra-Performance ® liquid chromatography (UPLC) in conjunction with time-of-flight mass spectrometry (TOFMS), we analyzed urine collected from rats prior to and at four time points after exposure to six different doses of gamma radiation ranging from 0.5 to 10 Gy at high dose rate.…”
Section: Introductionmentioning
confidence: 58%
“…Following 1 h incubation at 20 °C, microwells were washed four times and 100  μ l of tetramethylbenzidine (TMB, Thermo Scientific, Rockford, IL, USA) added for 15–30 min at 20 °C. Reactions were stopped by addition of 0.9 ℳ H 2 SO 4 (50  μ l) and product absorbance was determined at 450 nm (Partridge et al , 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Other cytokines shown to have potential influence on non-targeted effects include IL-6, Il-8, CCL2, CCL4, CCL7, CXCL7 and TNFα [12; 71; 92; 93]. Hei et al .…”
Section: Potential Mechanisms In the Mediation Of Non-targeted Effmentioning
confidence: 99%